Tough talk: Youth offenders’ perceptions of communicating in the Youth Justice system in New Zealand - Lount, Sarah A. (The Australian and New Zealand journal of criminology, 2017)
Youth Justice procedures rely heavily on oral language. International research suggests young people in the Youth Justice system have poorer language skills than their non-offending peers, which has implications for their participation in Youth Justice processes and rehabilitation programmes. Most research of youth offenders’ communication skills focuses on standardised assessments and quantitative measures, with little known of young people’s perceptions of communicating within the highly verbally mediated Youth Justice setting. This exploratory study used semi-structured interviews of eight males, of unknown language-skill status, from one Youth Justice residence in New Zealand. Results suggested the young people felt they had no control or ‘voice’ in court, or with adults whose roles, or with whom, they were not familiar. Communicating in court was an area of significant difficulty for nearly all the participants; they reported feeling unable to say what they wanted or understand what was going on. Confidence and participation varied with some participants lacking the confidence to use communication strategies in court, whereas others would ‘just say what they wanted’. The relationship with their communication partner, especially trust and familiarity, was very important to facilitate communication, and most young people could identify strategies that could help communication breakdowns, although not all reported using them. To facilitate full participation and access to court processes and Youth Justice programmes, the communication barriers identified in this study should be considered in any intervention or support developed for young people who offend.